Risk factors of incontinence-associated dermatitis among critically ill patients: A systematic review and meta-analysis - Jiang, Hongzhan; Shen, Jiali; Lin, Huihui; Xu, Qiuqin; Li, Yuanchan; Chen, Lijuan (Frontiers in Medicine, 2023)
Objectives: Incontinence-associated dermatitis (IAD) is increasingly found in critically ill patients, but the risk factors for IAD in these patients are currently unclear. This meta-analysis was designed to find out the risk factors of IAD in critically ill patients. Methods: Web of Science, PubMed, EMBASE, and Cochrane Library were systemically searched until July, 2022. Studies were selected according to inclusion criteria, and data was extracted by two researchers independently. The quality of included studies was evaluated with the Newcastle-Ottawa Scale (NOS). Odds ratios (ORs) and their corresponding 95% CIs were used to identify significant differences in the risk factors. Heterogeneity between studies was evaluated by the I2 test, and potential publication bias was assessed with Egger's test. Results: A total of 7 studies enrolling 1,238 recipients were included in the meta-analysis. Age ≥ 60 (OR=2.18, 95% CI: 1.38~3.42), female sex (OR=1.76, 95% CI: 1.32~2.34), dialysis (OR=2.67, 95% CI: 1.51~4.73), fever (OR=1.55, 95% CI: 1.03~2.33), vasoactive agent (OR=2.35, 95% CI: 1.45~3.80), PAT score ≥ 7 (OR=5.23, 95% CI: 3.15~8.99), frequency of bowel movement > 3times/d (OR=5.33, 95% CI: 3.19~8.93), and liquid stool (OR=2.61, 95% CI: 1.56~4.38) were associated with the risk factors of IAD among critically ill patients. Conclusions: Many risk factors are associated with IAD in critically ill patients. Nursing staff should pay more attention to assessing the risk of IAD and enhance the care of high-risk groups.